The Analysis of Student Learning Interest in Islamic Education (PAI) Course at Public Universiti in Bontang - Zulkifli, Zulkifli; Setiawan, Agus (el Buhuth: Borneo Journal of Islamic Studies, 2020)
This study aims to describe the factors of student interest in Islamic education courses at public universities in Bontang. The method used a quantitative research approach. Data collection used observation, interviews, and questionnaires by distributing google form to respondents. The research was conducted in two universities in Bontang that are University of Trunajaya with a total of 129 students and Bontang College of Technology (STITEK) with 71 students. The results showed that five indicators of students’ learning interest in PAI Bontang were: 1. attention, 2. like and pleasure, 3. pride and satisfaction, 4. interest, 5. Participation got the highest percentage on the indicator of pride, which is 22.57% or in a very good category. The lowest percentage was the indicator of interest in the Islamic education course, which is 20.02% or in the good category. Therefore, it could be concluded that the description of students’ learning interest is in a very good category, with a total score of 85.64.